Histological type of lung carcinoma in asbestos cement workers and matched controls. Issue 9 (September 1992) - Johansson, L; Albin, M; Jakobsson, K; Mikoczy, Z
Abstract : Histological types of lung carcinoma were examined in a case series of workers exposed to asbestos cement dust (n = 29) and matched controls (n = 87). The proportion of adenocarcinomas was 31% among the exposed subjects and 15% among the controls (mid-p = 0.05). Among workers with high exposure the proportion of adenocarcinoma was even higher (45%, 5/11; mid-p = 0.03). The proportion of peripheral tumours tended to be higher among exposed cases than controls (24 v 12%, mid-p = 0.12). Lobe of origin did not differ, however, between exposed cases and controls. Thus the study indicates an association between the degree of exposure to asbestos and adenocarcinoma of the lung, and a peripheral rather than central localisation of the tumours, but with virtually the same distribution of lobe of origin as in the general population.